Scientific dishonesty: European reflections. Issue 1 (1st January 2001) - Riis, P
Abstract : Scientific dishonesty has attracted increased attention around the world during the past three to four decades. Europe became aware of the problem later than the USA, but has within the past 10 years created national control systems for all biomedical projects, not only those supported by public money. The prevalence of the problem can only be calculated indirectly by referring to population figures as denominators. Measured this way, figures from Denmark as a whole show: 1–2 cases referred/million inhabitants/year, 1 case treated/million inhabitants/year, 1 case of scientific dishonesty/million inhabitants/5 years. For Finland, 1–2 cases were referred/million inhabitants/1–2 years; for Norway, similar figures of 1/4 million inhabitants/year were calculated. Figures from the Danish national independent control body 1993–7 show the distribution of the types of cases that were charged, with numbers of confirmed cases in parentheses: fabrication, 2 (1); plagiarism, 3 (0); theft, 2 (0); ghost authorship, 2 (1); false methodological description, 3 (1); twisted statistics, 2 (0); suppression of existing data, 4 (0); unwarranted use of data, 4 (0); and authorship problems, 8 (1). This survey emphasises the need for national guidelines, an independent national control body, and initiatives for strong preventive actions.